2022
DOI: 10.5194/os-18-51-2022
|View full text |Cite
|
Sign up to set email alerts
|

Arctic sea level variability from high-resolution model simulations and implications for the Arctic observing system

Abstract: Abstract. Two high-resolution model simulations are used to investigate the spatiotemporal variability of the Arctic Ocean sea level. The model simulations reveal barotropic sea level variability at periods of < 30 d, which is strongly captured by bottom pressure observations. The seasonal sea level variability is driven by volume exchanges with the Pacific and Atlantic oceans and the redistribution of the water by the wind. Halosteric effects due to river runoff and evaporation minus precipitation ice melt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This comparison is in agreement with expectations from earlier studies: although thermosteric effects dominate over halosteric effects over most of the global ocean, halosteric effects dominate in the Arctic Ocean because of the near-freezing water temperatures and the relatively low thermal expansion coefficient (Koldunov et al, 2014;Car-ret et al, 2017). Decadal freshwater variability in the Arctic Ocean has been the greatest contributor to observed SSH change (e.g., Xiao et al, 2020;Lyu et al, 2022), and freshwater changes have been shown to dominate projected SSH changes in CMIP6 under the SSP126 and SSP585 warming scenarios (e.g., Zanowski et al, 2021). In contrast to the contributions implied by SSS changes (Fig.…”
Section: Drivers Of Projected Summertime Ssh Trendsmentioning
confidence: 99%
“…This comparison is in agreement with expectations from earlier studies: although thermosteric effects dominate over halosteric effects over most of the global ocean, halosteric effects dominate in the Arctic Ocean because of the near-freezing water temperatures and the relatively low thermal expansion coefficient (Koldunov et al, 2014;Car-ret et al, 2017). Decadal freshwater variability in the Arctic Ocean has been the greatest contributor to observed SSH change (e.g., Xiao et al, 2020;Lyu et al, 2022), and freshwater changes have been shown to dominate projected SSH changes in CMIP6 under the SSP126 and SSP585 warming scenarios (e.g., Zanowski et al, 2021). In contrast to the contributions implied by SSS changes (Fig.…”
Section: Drivers Of Projected Summertime Ssh Trendsmentioning
confidence: 99%
“…The necessity to resolve such small scales makes it challenging to explicitly model mesoscale and submesoscale features in global climate models due to the lack of horizontal resolution. Recent developments in the ocean and coupled climate models, software, and hardware give a possibility for simulations with a very high horizontal resolution, for example, Wang et al (2020), Maslowski et al (2008), Regan et al (2020), Lyu et al (2022), andHordoir et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…The necessity to resolve such small scales makes it challenging to explicitly model submesoscale features in global climate models due to the lack of horizontal resolution. Recent developments in ocean climate models, software, and hardware give a possibility for simulations with a very high horizontal resolution, for example Wang et al (2020); Maslowski et al (2008); Regan et al (2020); Lyu et al (2022); Hordoir et al (2022).…”
Section: Introductionmentioning
confidence: 99%